IPO allocations: discriminatory or discretionary? - Ljungqvist, Alexander P; Wilhelm, William J (Journal of Financial Economics, 2002)
We estimate the structural links between IPO allocations, pre-market information production, and initial underpricing and find that (1) allocation policies favor institutional investors, both in the US and worldwide; (2) increasing institutional allocations results in offer prices that deviate more from the pre-marketing price range; (3) constraints on bankers’ discretion reduce institutional allocations and result in smaller price revisions, indicating diminished information production; and (4) initial returns are directly related to information production and inversely related to institutional allocations. Our results indicate that discretionary allocations promote price discovery in the IPO market and reduce indirect issuance costs for IPO firms.